Amyotrophic lateral sclerosis mutant TDP-43 may cause synaptic dysfunction through altered dendritic spine function - Tongcui Jiang; Emily Handley; Mariana Brizuela; Edgar Dawkins; Katherine E. A. Lewis; Rosemary M. Clark; Tracey C. Dickson; Catherine A. Blizzard (The Company of Biologists, 2019)
Altered cortical excitability and synapse dysfunction are early pathogenic events in amyotrophic lateral sclerosis (ALS) patients and animal models. Recent studies propose an important role for TAR DNA-binding protein 43 (TDP-43), the mislocalization and aggregation of which are key pathological features of ALS. However, the relationship between ALS-linked TDP-43 mutations, excitability and synaptic function is not fully understood. Here, we investigate the role of ALS-linked mutant TDP-43 in synapse formation by examining the morphological, immunocytochemical and excitability profile of transgenic mouse primary cortical pyramidal neurons that over-express human TDP-43A315T. In TDP-43A315T cortical neurons, dendritic spine density was significantly reduced compared to wild-type controls. TDP-43A315T over-expression increased the total levels of the α-amino-3-hydroxy-5-methyl-4-isoxazolepropinionic acid (AMPA) glutamate receptor subunit GluR1, yet the localization of GluR1 to the dendritic spine was reduced. These postsynaptic changes were coupled with a decrease in the amount of the presynaptic marker synaptophysin that colocalized with dendritic spines. Interestingly, action potential generation was reduced in TDP-43A315T pyramidal neurons. This work reveals a crucial effect of the over-expression mutation TDP-43A315T on the formation of synaptic structures and the recruitment of GluR1 to the synaptic membrane. This pathogenic effect may be mediated by cytoplasmic mislocalization of TDP-43A315T. Loss of synaptic GluR1, and reduced excitability within pyramidal neurons, implicates hypoexcitability and attenuated synaptic function in the pathogenic decline of neuronal function in TDP-43-associated ALS. Further studies into the mechanisms underlying AMPA receptor-mediated excitability changes within the ALS cortical circuitry may yield novel therapeutic targets for treatment of this devastating disease.